Introducing Saaralaa Mahaabhaarata - Bibudhendra Narayan Patnaik (My University, 2012)
Saaralaa Mahaabhaarata is said to be the first complete retelling by any one poet of the canonical text in an Indian Language. This monumental work has not been rendered into English. It is a truly wonderful retelling in verse in Odia of the classical Mahabharata story.
Sarala Mahabharath
Keywords: English